2013
DOI: 10.1039/c3py21151g
|View full text |Cite
|
Sign up to set email alerts
|

Reversible addition–fragmentation chain transfer polymerization of 2-chloro-1,3-butadiene

Abstract: Controlled polymerization of 2-chloro-1,3-butadiene using reversible addition-fragmentation chain transfer (RAFT) polymerization has been demonstrated for the first time. 2-Chloro-1,3-butadiene, more commonly known as chloroprene, has significant industrial relevance as a crosslinked rubber, with uses ranging from adhesives to integral automotive components. However, problems surrounding the inherent toxicity of the lifecycle of the thiourea-vulcanized rubber have led to the need for control over the synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…All systems were shown to exhibit identical pseudo‐first‐order rate plots during the early stages of polymerisation. However, for the polymerisation of 2‐chloro‐1,3‐butadiene (CB), our group recently found that the solvent had a marked effect over the control and rate of PCB synthesis, with THF showing enhanced control over xylene . Similarly, Abreu et al showed distinct differences on the polymerisation of vinyl chloride performed in DCM, cyclohexanone and THF, once again with THF giving rise to the most successful results.…”
Section: Resultsmentioning
confidence: 99%
“…All systems were shown to exhibit identical pseudo‐first‐order rate plots during the early stages of polymerisation. However, for the polymerisation of 2‐chloro‐1,3‐butadiene (CB), our group recently found that the solvent had a marked effect over the control and rate of PCB synthesis, with THF showing enhanced control over xylene . Similarly, Abreu et al showed distinct differences on the polymerisation of vinyl chloride performed in DCM, cyclohexanone and THF, once again with THF giving rise to the most successful results.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike previous studies concerning the RAFT polymerization of CP in organic solvents (e.g., THF, benzene, and xylene), 16,17 this contribution represents the first report of the controlled emulsion polymerization of CP via the RAFT process using a suitable combination of nonionic surfactant and dithiocarbamate-type RAFT agent. The aim of this work is to identify strategies to perform the controlled RAFT-mediated emulsion polymerization of CP using a suitable RAFT agent and emulsifier under industrially applicable conditions, which are required to realize large-scale production.…”
Section: Introductionmentioning
confidence: 93%
“…8 RAFT polymerization has also been employed to synthesize block and miktoarm star polymers composed of acrylonitrile and butadiene, 7,9 and structured nanoparticles composed of styrene and butadiene. 16 Hui et al demonstrated that RAFT polymerization of CP in benzene using the dithiobenzoate-type RAFT agents afforded poly(CP)s with predetermined molecular weights and low molar mass dispersities. The difficulty in adapting controlled radical polymerization to CP mainly arises from the fact that the monomer is highly polar and shows a high degree of homopolymerizability, which originate from the electron-rich vinyl group and the electronegative chlorine atom.…”
Section: Introductionmentioning
confidence: 99%
“…Pullan et al investigated RAFT solution polymerization of chloroprene with one of CPDB ( 6 ), 14 , DDMAT ( 20 ) or 36 as RAFT agent, AIBN as initiator and either xylene or THF as solvent at 60 °C (Table , entries B–J). Not surprisingly no control was observed with the dithiocarbamate 36 .…”
Section: Raft (Co)polymerization Of Diene Monomers In Solutionmentioning
confidence: 99%
“…Pullan et al showed that it was possible to chain extend isolated polychloroprene dithiobenzoate with chloroprene. Hui et al found it was not possible chain extend polychloroprene dithiobenzoate with MMA or styrene.…”
Section: Raft (Co)polymerization Of Diene Monomers In Solutionmentioning
confidence: 99%